The Development and Purposes of Farm-Cost Investigation in the United States - Bennett, M. K. (Quarterly Journal of Economics, 1926)
I. Four methods of collecting cost data: route method, survey method, questionnaire, farmer's record, 274. — History of the movement, 275. — II. Influences promoting the movement, 277. — Efficiency, country life, tariff inquiries, cost in relation to price, 278. — III. Price-fixing as an object, 283. — Farm efficiency, 284. — IV. Difficulties in the way of accuracy, 286. — How deal with managerial ability, rent and land value, joint costs, 287. — Cost records of doubtful value; problems of averaging, 287. — Not easy to advise farmers what to produce, 291. — Conclusion, 293.